Book byte and beyond library without walls - Mahapatra, Piyush Kanti; Chakrabarti, Bhubaneswar (New Delhi Ess Ess, 2000)
Book byte and beyond is a library science book.The main contents are-Ancestors of the book,changing face of libraries,electronic publishing,Database development,Electronic publishing,Digital library and internet and the future are the main feature of the
Keywords: Libraries-India; Digital libraries-India; Information storage and retrieval systems; Computer science-Digital libraries